Konsep Uang dalam Perspektif Ekonomi Islam dan Ekonomi Konvensional - Ahmad Mansur (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
Money which is the most liquid asset, is also commodity in the economy. It can be traded just as goods and services. Everybody has an access to enter money market and sell the money to those who demand it either for consumption, production and investment at the market price. The concept of money then is identical to the capital, this lead to the practice of interest in the money market because interest is considered the price of the use of money. The involvement of the interest in the money market can be traced from its theory of money demand and from the function of money itself as store of value and as standard of deferred payment, besides as medium of exchange and as unit of account or measure of value.In the perspective of an Islamic economics, the function of money is only as medium of exchange and as unit of account. Since money is not commodity it can not be traded in the economy. That is why money is not identical to the capital, as result it also can not be kept for a long period of time. It must be circulated in the society and be used to perform economic activity. So in an Islamic economics money is flow concept and not stock concept, money is public property and not individual property. This distinction of the concept of money in the conventional economics and in an Islamic economics can be traced from its function and its theory of money demand which both of them have advantages and disadvantages. For example, the concept of money in an Islamic economic tends to make money always circulate and flow among society to be used for the economic activity while in the conventional economic money tends to be kept idle as individual wealth and will be released only if its price is quite high in the market. It is not necessary however to force ourselves applying to one concept and leaving the other one, but let both of them go hand in hand and complement each other in economy.